2000
DOI: 10.1149/1.1394085
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Ethylenetetrafluoroethylene-g-polystyrenesulfonic Acid Solid Polymer Electrolytes

Abstract: Proton-exchange-membrane fuel cells (PEMFCs) have received considerable interest as a reliable power source due to their ability to attain high power densities with high energy efficiency. 1 A vital component of the PEMFC is the proton exchange membrane (PEM), which provides the ionic path between the anode and the cathode while separating the two reactant gases. The PEM material most frequently used for this type of application is Nafion ® due to its chemical and mechanical stability and its commercial availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…New bands were observed; these were present in the Raman spectrum of poly(vinylbenzyl chloride). The most significant of these were strong bands at 1613, 1268, 1003 cm -1 , the latter of which was the most intense and was also present as the 12 band in the spectrum of poly(styrene). 22 There was evidence of a small amount of residual VBC monomer in the material (a band at 1632 cm -1 in the Raman spectrum of F1 -see thermogravimetry of F1 later); this feature corresponds to the strong C=C band located in the Raman spectrum of VBC, which does not occur in the spectrum of poly(vinylbenzyl chloride).…”
Section: Characterisation By Vibrational Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…New bands were observed; these were present in the Raman spectrum of poly(vinylbenzyl chloride). The most significant of these were strong bands at 1613, 1268, 1003 cm -1 , the latter of which was the most intense and was also present as the 12 band in the spectrum of poly(styrene). 22 There was evidence of a small amount of residual VBC monomer in the material (a band at 1632 cm -1 in the Raman spectrum of F1 -see thermogravimetry of F1 later); this feature corresponds to the strong C=C band located in the Raman spectrum of VBC, which does not occur in the spectrum of poly(vinylbenzyl chloride).…”
Section: Characterisation By Vibrational Spectroscopymentioning
confidence: 99%
“…21 The new bands observed were all present in the Raman spectrum of poly(vinylbenzyl chloride). The most significant of these were strong bands at 1613, 1269, 1003 cm -1 , the latter of which was the most intense and was also present as the 12 band in the Raman spectrum of poly(styrene). 22 Bands at 1633 and 1408 cm -1 in the spectrum of VBC associated with the C=C str.…”
Section: Characterisation By Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, DAIS membranes are being promoted for the low temperature (<60 °C) portable fuel cell power market. In the grafting strategy, thermally and chemically stable fluorinated polymers (fluorinated ethylene propylene (FEP) [95,96]) or partially fluorinated polymers [ethylene tetrafluoroethylene (ETFE) [97,98] or polyvinylidene fluoride (PVDF) [99]] were chosen as the base polymers and shown to produce materials with some improved performance. It has been reported that the most stable polystyrene analogue is a vinyl perfluorosulfonic system developed by Ballard Power [100].…”
Section: Poly (Styrene Sulfonic Acid) (Pssa)mentioning
confidence: 99%
“…A significant proportion of previous fuel cell membrane research has examined the radiation-grafting of styrene onto polyethylene films, partially fluorinated films such as poly(vinylidene fluoride) (PVDF) and poly(ethylene-co-tetrafluoroethylene) (ETFE), and fully fluorinated poly(tetrafluoroethene-co-hexafluoropropylene) (FEP) films with subsequent sulfonation to yield cation-exchange sites [8][9][10][11][12][13][14][15], the properties and compositions of the final materials being easily controlled [8,12]. Such protonexchange membranes have been tested in DMFC mode by Scott et al [16].…”
Section: Introductionmentioning
confidence: 99%